2021
DOI: 10.2147/ijn.s277014
|View full text |Cite
|
Sign up to set email alerts
|

ROS-Mediated Apoptosis and Autophagy in Ovarian Cancer Cells Treated with Peanut-Shaped Gold Nanoparticles

Abstract: Background Even with considerable improvement in treatment of epithelial ovarian cancer achieved in recent years, an increasing chemotherapy resistance and disease 5-year relapse is recorded for a majority part of patients that encourages the search for better therapeutic options. Gold nanoparticles (Au NPs) due to plethora of unique physiochemical features are thoroughly tested as drug delivery, radiosensitizers, as well as photothermal and photodynamic therapy agents. Importantly, due to highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 71 publications
3
28
0
Order By: Relevance
“…In the majority of reported studies, gold nanorods were also characterized by higher cellular uptake efficiency, thus presenting an improved drug delivery efficiency when compared with spherical ones [50,51]. Indeed, our previous research revealed that peanut-shaped gold nanoparticles are far more effective against cancer cells than those spherical ones ( [22]; see Supplementary Materials). Moreover, a nanosystem consisting of CSA-131 attached to the surface of spherical-shaped gold NPs was not efficient enough against ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the majority of reported studies, gold nanorods were also characterized by higher cellular uptake efficiency, thus presenting an improved drug delivery efficiency when compared with spherical ones [50,51]. Indeed, our previous research revealed that peanut-shaped gold nanoparticles are far more effective against cancer cells than those spherical ones ( [22]; see Supplementary Materials). Moreover, a nanosystem consisting of CSA-131 attached to the surface of spherical-shaped gold NPs was not efficient enough against ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Immunostaining of cells exposed to CSA-131 and AuP@CSA-131 for 72 h was performed in order to visualize alterations in the expression of proteins related to cell killing processes. For this purpose, treated SKOV-3 cells were fixed, permeabilized, blocked with 0.1% bovine serum albumin (BSA) and incubated with antibodies against apoptotic (NOX4, annexin A1, cleaved caspase-3, cleaved caspase-9) and autophagic proteins (Atg12 and Beclin-1) according to the previously presented protocol [22].…”
Section: Immunofluorescence Staining Of Apoptosis and Autophagy-related Proteinsmentioning
confidence: 99%
See 3 more Smart Citations